From terminology to terminology services. - Nowlan, W. A. (American Medical Informatics Association, 1994)
Terminologies have traditionally been considered as static datasets held in books or databases. The GALEN Terminology Server presents a prototype for a new view of terminologies delivered as a set of functions and services provided to other applications. This facilitates their development and integration as part of a strategy for sharing and re-using information and knowledge. The essential features of the Terminology server are the functions which it can perform; questions which it can answer and statements which it can be told. The GALEN Terminology Server supports these operations through a modular architecture and uniform applications programming interface which allows client applications to ignore the internal structure and simply use the Server for terminological, coding, and linguistic functions.